Comparative genomics of Staphylococcus capitis reveals species determinants - Chong, Charlotte E.; Bengtsson, Rebecca J.; Horsburgh, Malcolm James (Frontiers in Microbiology, 2022)
Staphylococcus capitis is primarily described as a human skin commensal but is now emergent as an opportunistic pathogen isolated from the bloodstream and prosthetic joint infections, and neonatal intensive care unit (NICU)-associated sepsis. We used comparative genomic analyses of S. capitis to provide new insights into commensal scalp isolates from varying skin states (healthy, dandruff lesional, and non-lesional), and to expand our current knowledge of the species populations (scalp isolates, n = 59; other skin isolates, n = 7; publicly available isolates, n = 120). A highly recombinogenic population structure was revealed, with genomes including the presence of a range of previously described staphylococcal virulence factors, cell wall-associated proteins, and two-component systems. Genomic differences between the two described S. capitis subspecies were explored, which revealed the determinants associated exclusively with each subspecies. The subspecies ureolyticus was distinguished from subspecies capitis based on the differences in antimicrobial resistance genes, β-lactam resistance genes, and β-class phenol soluble modulins and gene clusters linked to biofilm formation and survival on skin. This study will aid further research into the classification of S. capitis and virulence-linked phylogroups to monitor the spread and evolution of S. capitis.